2010
DOI: 10.1093/alcalc/agq013
|View full text |Cite
|
Sign up to set email alerts
|

RCT of Effectiveness of Motivational Enhancement Therapy Delivered by Nurses for Hazardous Drinkers in Primary Care Units in Thailand

Abstract: MET delivered by nurses in PCUs in Thailand appears to be an effective intervention for male hazardous drinkers. Uncertainties about the validity of self-reported data jeopardize the safety of this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 15 publications
(16 reference statements)
1
82
0
1
Order By: Relevance
“…However, the webbased setting allowed for anonymity and privacy, both of which can increase reports of sensitive information, and studies in treatment settings generally suggest that carefully collected self-reported alcohol data are reliable [65]. There have not yet, however, been online or brief intervention studies that have reached similar conclusions [66]. We tested our models by removing outliers, which changed the results minimally.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, the webbased setting allowed for anonymity and privacy, both of which can increase reports of sensitive information, and studies in treatment settings generally suggest that carefully collected self-reported alcohol data are reliable [65]. There have not yet, however, been online or brief intervention studies that have reached similar conclusions [66]. We tested our models by removing outliers, which changed the results minimally.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Better understanding of the technical limitations of this validation approach is necessary in order to evaluate the validity of the self-reported data. This is an issue that also deserves attention in brief interventions for alcohol where validation studies in treatment contexts may be less informative than well-established problems of underreporting in general population surveys [13].…”
Section: Commentary On Schwartz Et Al (2014): Where Next For Face-tomentioning
confidence: 99%
“…Better understanding of the technical limitations of this validation approach is necessary in order to evaluate the validity of the self-reported data. This is an issue that also deserves attention in brief interventions for alcohol where validation studies in treatment contexts may be less informative than well-established problems of underreporting in general population surveys [13].The implications of these findings are somewhat challenging to elaborate because of uncertainties in the wider research context. The authors hypothesized that the computerized intervention would outperform faceto-face brief intervention, because having a conversation about drug use in primary care when one is not seeking help may be difficult [8].…”
mentioning
confidence: 99%
“…However, a few studies confirm that implementing alcohol treatment methods typically used overseas, such as motivational interviewing (MI) and brief intervention (BI), can be useful tools for reducing alcohol consumption. BI has been applied by community nurses that deliver consultations to people experiencing alcohol addiction and abuse in Thailand (Areesantichai, Chapman, & Perngparn, 2013;Areesantichai, Iamsupasit, Marsden, Perngparn, & Taneepanichskul, 2010;Noknoy, Rangsin, Saengcharnchai, Tantibhaedhyangkul, & McCambridge, 2010;Srikosai et al, 2008). However, one of these studies revealed that the effectiveness of the findings could not be measured since both the interventions and patients' reports concerning their drinking culture occurred during 'the Buddhist Lent'.…”
Section: Introductionmentioning
confidence: 99%
“…During this three-month-long observation, people do good deeds (e.g. avoid or stop drinking); after this period, however, normal drinking patterns are typically resumed (Noknoy et al, 2010). The Mental Health Department of Thailand implemented MI, BI, motivational enhancement therapy (MET), and cognitive behavior therapy (CBT) for alcohol treatment; the report of these implementations questioned if the healthcare providers had sufficient knowledge and skill to treat alcohol addiction and abuse (Kittirattanaphiboon & Jumroonsawat, 2011).…”
Section: Introductionmentioning
confidence: 99%